Walking on water : reflections on faith & art - L'Engle, Madeleine (Wheaton, Ill. : H. Shaw, 1980)
In this classic book, Madeleine L'Engle addresses the questions, What makes art Christian? What does it mean to be a Christian artist? What is the relationship between faith and art? Through L'Engle's beautiful and insightful essay, readers will find themselves called to what the author views as the prime tasks of an artist: to listen, to remain aware, and to respond to creation through one's own art.
Keywords: Christianity and the arts; L'Engle, Madeleine